"Passing the trash" by the Michigan Board of Education - Crandall, William, 1956- (SAGE knowledge. Cases., 2016)
This case discusses the crisis that was generated by the Michigan Board of Education's decision to cover up the sexual assaults of minors committed by one of their teachers. Instead the teacher was allowed to resign quietly and was eventually rehired by another school where he was free to strike again, causing further emotional trauma and financial damage.